Embodied interactions with adaptive architecture - Jäger, Nils; Schnädelbach, Holger; Hale, Jonathan (Springer, 2016)
We discuss increasingly behaviour-responsive adaptive architecture from an embodied point of view. Especially useful in this context is an understanding of embodied cognition called ‘the 4E approach,’ which includes embodied, extended, embedded, and enacted perspectives on embodiment. We argue that these four characteristics of cognition both apply to and explain the bodily interactions between inhabitants and their adaptive environments. However, a new class of adaptive environments now expands this notion of embodied interactions by introducing environment-initiated behaviours, in addition to purely responsive behaviours. Thus, we consider how these new environments add the dimension of bodily reciprocity to Adaptive Architecture.